Reverse Engineering Analysis Forensic Malware WEBC2-DIV - Waliulu, Raditya Faisal; Iskandar Alam, Teguh Hidayat (Politeknik Ganesha Medan, 2018)
At this paper focus on Malicous Software also known as Malware APT1 (Advance Presistent Threat) codename WEBC2-DIV the most variants malware has criteria consists of Virus, Worm, Trojan, Adware, Spyware, Backdoor either Rootkit. Although, malware could avoidance scanning antivirus but reverse engineering could be know how dangerous malware infect computer client. Lately, malware attack as a form espionage (cyberwar) one of the most topic on security internet, because of has massive impact. Forensic malware becomes indicator sucessfull user to relized about malware infect. This research about reverse engineering. A few steps there are scanning, suspected packet in network and analysis of malware behavior and dissambler body malware.